A paz como direito humano: possibilidades e alternativas da fórmula estado de direito - Ferreira Neto, Hélio Gois (2014)
The United Nations elected the Rule of Law, in combination with human rights, democracy and development as the political algorithm which supposedly would deliver the promise of Peace to mankind. Within this context, the human right to peace was normatively set by the UN, tough without a theoretical foundation to support it. The first part of this essay of mainly propaedeutic nature, it is exposed the paradigms of drudgery: the Civilization Process Theory and the Symbolic Theory of Norbert Elias; the Theory of Truth of Susan Haack; the Theory of Power of John K. Galbraith; and the Theory of Values, under a philosophical prism. Those parameters have as much defied neo-Hobbesian positions that defend a human tendency to violence as they serve for the analysis of the reasons de facto which brought the UN to the political algorithm it preaches about; but, also, they suggest the peace virtually displays itself as a possibility. In the second part, investigates the reasons that took the UN to such choices and the identification of the theoretical framework that influenced it, presenting the existing similitudes with the jusnaturalist thought of Gustav Radbruch; but, also, it considers the insufficiency of the Kantian paradigm for analyzing questions that go beyond the modernity paradigm marked by freedom or even by peace as supreme value. In the third part, there is a review of the whole question within a civilizatory context and the proposed parameters, showing that the replacement of freedom by peace as the supreme value with the UN system does not present itself as the best solution just because it will not assure peace; this is due because peace is not the supreme value in any scenario, remarkably when already established the conflict, as it is replaced by other values which are superior in those cases, e.g. survivorship. But, also, the reasons by which it is verified that the axiological compass suggested by the UN, as source of the Rule of Law displays itself out of date for facing the challenges of the XXI century, such as the phenomenon of globalization, and how this has been affecting the structure of the UN’s compounding parties, the national States.